Hemicellulases from Penicillium and Talaromyces for lignocellulosic biomass valorization: A review. (March 2021) - Méndez-Líter, Juan A.; de Eugenio, Laura I.; Nieto-Domínguez, Manuel; Prieto, Alicia; Martínez, María Jesús
Abstract: The term hemicellulose groups different polysaccharides with heterogeneous structures, mannans, xyloglucans, mixed-linkage β-glucans and xylans, which differ in their backbone and branches, and in the type and distribution of glycosidic linkages. The enzymatic degradation of these complex polymers requires the concerted action of multiple hemicellulases and auxiliary enzymes. Most commercial enzymes are produced by Trichoderma and Aspergillus species, but recent studies have disclosed Penicillium and Talaromyces as promising sources of hemicellulases. In this review, we summarize the current knowledge on the hemicellulolytic system of these genera, and the role of hemicellulases in the disruption and synthesis of glycosidic bonds. In both cases, the enzymes from Penicillium and Talaromyces represent an interesting alternative for valorization of lignocellulosic biomass in the current framework of circular economy.